East and West Space in the Cultural Picture of the World (Linguocultural Experiment) - Konyratbayeva, Ж.М. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
World-image is one of the studied objects in the research of intercultural communication, as well as cultural world-image. The article is devoted to the analysis of the cultural world-image of the East and West from the linguo-cultural point of view and describes the map of civilizations through the eyes of the students. During the creation of the cultural map, a linguocultural experiment was conducted among the students in three thematic areas. For each topic an example was given in the volume of 5-10 words and two cultures were interpreted from the point of cultural-linguistic aspect. Linguistic and cultural experiment was conducted in 2011-2012, 2013-2014 and 2016-2017 academic years among students of the Faculty of Philology. The purpose of this article is the unity of the East and West in the culturalworld-image, creation of it’s map and consideration of topical issues of intercultural communication. By means of trip to the cultural space of East and West, we were able to determine the cultural and cognitive stereotypes of the youth of Kazakhstan, the world view and culture of different peoples, and get more acquainted with national values.